Are There Misconceptions in My Class? Misconception Analysis with T3-SF (Three Tier-Test on Static Fluid) - Atmaja, Devi Yulianty Surya; Samsudin, Achmad (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
This study aims to identify the misconceptions of 20 students in class XI MIPA in one of the Senior High Schools in Sumedang Regency, Indonesia. The selection of research subjects used a random sampling technique. This research used a descriptive qualitative research design with a case study approach. The data collection technique in this study used T3-SF (Three Tier-Test on Static Fluid) to identify misconceptions in the submaterial of Hydrostatic Pressure, Pascal's Law and Archimedes' Law. Students did ten questions on Google Forms and processed them using Microsoft Excel. Based on this study, the majority of students, 88.5%, have misconceptions, 9% have understood the concept and 2.5% of students are in the category of not understanding the concept. It can be concluded that three concepts of static fluid, namely Hydrostatic Pressure, Pascal's Law and Archimedes' Law, are at a high level of misconception because more than 61%. Students of Pascal's Law material experience a high level of misconception (100%). Meanwhile, the lowest misconception from other question numbers is the question for Archimedes' Law material. The researcher also recommends that future studies further classify the misconception category into partial misconceptions, false negatives and false positives.